(3TQM UMjM GdHNGQis - (3CHh SdjeGf CMeO Hf eMMeO Hf EHQGgje GdNWGHi GdHSJfis; (3eMeO Hf ESeGYjd Hf EHQGgje Hf GdeZjQI GdHNGQj, CHh YHO Gddg,J (B256 (3g` s
(3ChdgG (B:s
(3jHJOF HChd GdcJGH s
(3BNQgG (B:s
(3hjfJgi HHG bhdg YR hLd (B:" (3jG CjgG GdPjf BefhG TgGOI Hjfce s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B84 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(21435(3H(B) s
Keywords: (3GdMOjK h GdeUWdMs